Pengaruh Kualitas Layanan Kawasan Wisata Pantai Carocok Painan terhadap Kepuasan Wisatawan - Abror, Abror; Thabrani, Gesit; Elfani, Riyeni Dwi (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2013)
The purpose of this research is to examine the effects of service quality to the tourist’s satisfaction in The Coast of Carocok Painan area. Population in this research is all tourists at the Coast of Carocok Painan area. Total respondents are 100 respondents, the sample determined by using nonprobability sampling, namely accidental sampling. Data in this research was primary data which had been collected through questionnaire. Multiple regression was used to analyse the data by using application processor of data of SPSS 16. The result of the researh indicates that tangibles, responsiveness and assurance dimension has a positive effect and significant to the tourists satisfaction. Reliability and empathy dimension do not have positive and significant effect to the tourists satisfaction.